Effects of semaglutide on vascular structure and proteomics in high-fat diet-induced obese mice - Yue, Lin; Chen, Shuchun; Ren, Qingjuan; Niu, Shu; Pan, Xiaoyu; Chen, Xing; Li, Zelin; Chen, Xiaoyi (Frontiers in Endocrinology, 2022)
Background: Obesity is a chronic metabolic disease caused by a combination of genetic and environmental factors. To determine whether semaglutide could improve aortic injury in obese C57BL/6J mice, and further explore its molecular mechanism of action using proteomics. Methods: 24 C57BL/6J male mice were randomly divided into normal diet group (NCD group), high-fat diet group (HFD group) and high-fat diet + semaglutide group (Sema group, semaglutide (30 nmol/kg/d) for 12 weeks). The serum samples were collected from mice to detect blood glucose, insulin and blood lipid concentrations. Aortic stiffness was detected by Doppler pulse wave velocity (PWV). Changes in vascular structure were detected by HE, masson, EVG staining and electron microscopy. The aorta-related protein expression profiles were detected by proteomic techniques, and proteins with potential molecular mechanisms were identified. Results: Semaglutide could reduce body weight, the concentrations of blood glucose, total cholesterol (TC), triglycerides (TG), lipoprotein cholesterol (LDL-C), and reduce the aortic PWV and ameliorate vascular damage in obese mice. The results of proteomic analysis showed there were 537 up-regulated differentially expressed proteins (DEPs) and 322 down-regulated DEPs in NCD/HFD group, 251 up-regulated DEPs and 237 down-regulated proteins in HFD/Sema group. There were a total of 25 meaningful overlapping DEPs in the NCD/HFD and HFD/Sema groups. GO enrichment analysis of overlapping DEPs found that these differential proteins were mainly located in the signaling pathways of the extracellular matrix. The most obvious changes of extracellular matrix associated proteins in the three experimental groups were Coll5a1, Lama4, Sparc. Conclusion: Semaglutide may protect vascular structure and improve endothelial permeability by reducing the levels of Coll5a1, Lama4, Sparc in extracellular matrix, so as to improve vascular function and achieve vascular protection.